Letter to the editor: Six‐month antibody kinetics and durability in liver transplant recipients after two doses of SARS‐CoV‐2 mRNA vaccination. Issue 10 (5th July 2022) - Chang, Amy; Strauss, Alexandra T.; Alejo, Jennifer L.; Chiang, Teresa P.‐Y.; Hernandez, Nicole F.; Zeiser, Laura B.; Boyarsky, Brian J.; Avery, Robin K.; Tobian, Aaron A. R.; Levan, Macey L.; Warren, Daniel S.; Garonzik‐Wang, Jacqueline M.; et al.
Abstract : image